Antifungal and genotoxic effects of Thymus serpyllum as a root canal irrigant - Ariana Kameri; Agime Dragidella; Arben Haziri; Zeqir Hashani; Kemajl Kurteshi; Arsim Kurti (Wiley, 2024)
Abstract Objectives The aim of this study was the assessment of the efficiency of the ethyl acetate (EthOAc) extract of Thymus serpyllum against Candida albicans and to compare it with sodium hypochlorite (NaOCl) and chlorhexidine (CHX), as well as their genotoxic effect. Material and Methods The antifungal effectiveness of the EthOAc extract of Thymus serpyllum was determined using the agar disk diffusion method. The inhibition zones induced by the EthOAc extract were compared after 5 min, 60 min, and 24 h to those induced by standard solutions (2% CHX and 2% NaOCl). An in vitro genotoxicity assay was performed in cultured lymphocytes from the blood of human volunteers to observe micronuclei formation. Statistical analysis of the results was performed using the Kruskal-Wallis test and one‐way analysis of variance. Results The inhibition zone of combination of CHX with EthOAc extract of Thymus serpyllum against C. albicans was 29.7 mm after 5 min, 28.3 mm after 60 min, and 29 mm after 24 h. The inhibition zone of NaOCl in combination with EthOAc extract of Thymus serpyllum against C. albicans was 0 mm. The EthOAc extract of Thymus serpyllum did not show a genotoxic effect on lymphocyte cells. Conclusions The EthOAc extract of Thymus serpyllum in combination with CHX may be a useful root canal disinfection in endodontic therapy.